2021
DOI: 10.35848/1347-4065/ac1645
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of reduction-resistant lead-free NaNbO3–BaTiO3 piezoelectric ceramics

Abstract: Lead-free NaNbO 3 -BaTiO 3 piezoelectric ceramics were fabricated under a low oxygen partial pressure, which enables co-sintering with base metal Ni electrodes. The reducing atmosphere was accurately controlled by adopting a suitable mixture of Ar, H 2 , and CO 2 gases. By adding MnCO 3 , ZrO 2 , and Li 2 CO 3 , resultant NaNbO 3 -BaTiO 3 ceramics sintered in a reducing atmosphere have high resistivities, maintain high sintering densities, and exhibit piezoelectric constants equivalent or superior to samples p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[ 17 ] Meanwhile, it is reported that NaNbO 3 ‐based ceramics can be co‐fired with base metal Ni electrodes in a reducing atmosphere, taking advantage of the stable valence state of Nb 5+ . [ 18 ] Considering its exceptional energy storage characteristics and adaptability to various preparation environments, NN emerges as a highly suitable material for developing lead‐free MLCCs intended for actual applications. However, there has been limited research on NN‐based MLCCs, and the existing related investigations primarily focus on materials showing the AFE features.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Meanwhile, it is reported that NaNbO 3 ‐based ceramics can be co‐fired with base metal Ni electrodes in a reducing atmosphere, taking advantage of the stable valence state of Nb 5+ . [ 18 ] Considering its exceptional energy storage characteristics and adaptability to various preparation environments, NN emerges as a highly suitable material for developing lead‐free MLCCs intended for actual applications. However, there has been limited research on NN‐based MLCCs, and the existing related investigations primarily focus on materials showing the AFE features.…”
Section: Introductionmentioning
confidence: 99%
“…Although barium titanate-based materials have several advantageous properties, their lowtemperature stability of piezoelectric properties has hindered their widespread use in technology. The study of the solid solution of Sodium niobate and Barium Titanate has been an area of significant interest [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…However, piezoelectric materials implemented to date relied on lead zirconate titanate (PZT), which is regulated in Europe. Although lead-free piezoelectric materials are being developed, [15][16][17][18] their output power remained low compared to those of PZTs.…”
Section: Introductionmentioning
confidence: 99%